Contabilidad de gestión en las empresas y el proceso de toma de decisiones (2023)
This work aims to carry out a review of the advances in research during recent years in the area of ​​management accounting and its application to processes management and decision-making, such as the application of tools and systems management have allowed for increased efficiency and competitiveness.